A multi-omics approach reveals dysregulated TNF-related signaling pathways in circulating NK and T cell subsets of young children with autism - Wared Nour-Eldine (13904298) (2025)
Peripheral immune dysregulation is frequently reported in autism spectrum disorder (ASD); however, the underlying molecular mechanisms remain unclear. We recruited a well-defined cohort of young Arab children with ASD, aged 2–4 years, along with matched controls in Qatar. Using a multimodal approach, we integrated transcriptomic, proteomic, and single-cell RNA-seq data analyses from this cohort. Targeted transcriptomic profiling identified differential expression of 50 immune-related genes in the circulating PBMCs of children with ASD, three of which (JAK3, CUL2, and CARD11) negatively correlated with ASD symptom severity. These gene signatures were validated in independent studies using blood and brain tissues from individuals with ASD. Enrichment analysis revealed involvement of these genes in immune function, particularly through TNF signaling pathway. Proteomic analysis highlighted disrupted TNF signaling and upregulated levels of TNFSF10 (TRAIL), TNFSF11 (RANKL), and TNFSF12 (TWEAK) in plasma of individuals with ASD. Single-cell RNA-seq revealed that B cells, CD4 T cells, and NK cells potentially contributed to these upregulations in ASD. Dysregulated TRAIL, RANKL, and TWEAK signaling pathways were specifically observed in CD8 T cells, CD4 T cells, and NK cells of individuals with ASD. These findings provide new insights into immune dysregulation mechanisms in ASD and highlight potential therapeutic targets. Other Information Published in: Genes & Immunity License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41435-025-00349-z